2020
DOI: 10.1001/jama.2020.17386
|View full text |Cite
|
Sign up to set email alerts
|

Racial/Ethnic Variation in Nasal Gene Expression of Transmembrane Serine Protease 2 (TMPRSS2)

Abstract: Discussion | This study of nasal epithelial gene expression in a racially/ethnically diverse cohort showed significantly higher expression of TMPRSS2 in Black individuals compared with other self-identified races/ethnicities. Given the essential role of TMPRSS2 in SARS-CoV-2 entry, 3 higher nasal expression of TMPRSS2 may contribute to the higher burden of COVID-19 among Black individuals. TMPRSS2 inhibitors such as camostat mesylate 3 are undergoing clinical trials to test their utility for COVID-19 treatment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
47
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(48 citation statements)
references
References 5 publications
0
47
0
1
Order By: Relevance
“…Moreover, using public gene expression datasets, a differential expression was found not only for ACE2 but also for the TMPRSS2 gene in the nasal and bronchial airways in relation to age ( 41 ). Interestingly, it was found a higher TMPRSS2 expression on nasal epithelial cells from Black individuals than Asian, Latino, and White individuals ( 42 ). These finding could explain the 2–3 times higher incidence of COVID-19 among Black individuals ( 43 ).…”
Section: Ace2/adam17 In Covid-19’s Comorbiditiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, using public gene expression datasets, a differential expression was found not only for ACE2 but also for the TMPRSS2 gene in the nasal and bronchial airways in relation to age ( 41 ). Interestingly, it was found a higher TMPRSS2 expression on nasal epithelial cells from Black individuals than Asian, Latino, and White individuals ( 42 ). These finding could explain the 2–3 times higher incidence of COVID-19 among Black individuals ( 43 ).…”
Section: Ace2/adam17 In Covid-19’s Comorbiditiesmentioning
confidence: 99%
“…However, it is still unknown whether ACE2 cleavage by both proteases is mutually exclusive or not, and the relevance of the interplay of these mechanisms on the pathophysiology of COVID-19. In this scenario, it can be expected that increased expression of TMPRSS2 induced by androgen hormones or the occurrence of specific genetic variants ( 5 , 42 , 121 ), or both factors together, may lead to exacerbate, even more, the ACE2 cleavage—mediated harmful effects, by decreasing the membrane-bound or soluble biologically active ACE2 forms.…”
Section: Ace2/adam17/tmprss2 Underlying Risk Factors For Covid-19mentioning
confidence: 99%
See 1 more Smart Citation
“…Lowering the excess prevalence of comorbid conditions such as obesity, diabetes and hypertension in minority populations [ 37 ] should be a public health priority. Higher rates of SARS-CoV-2 infection seen across all age groups rather than differences in age-adjusted case-fatality rates suggest that a primary cause of racial disparity in COVID-19 may be differences in household, community and workplace exposure [ 37 , 38 ], although biological factors may also be contributory [ 39 ].…”
Section: Epidemiologymentioning
confidence: 99%
“…A serine protease TMPRSS2 on nasal and bronchial epithelium is important in coronavirus infection ( 47 ). Bunyavanich and colleagues showed that TMPRS22 expression was significantly higher in Black compared to Asian, Latino, mixed race, and White individuals ( 48 ).…”
Section: If Activation By Cortisol Of the Mineralocorticoid Receptormentioning
confidence: 99%